Local Norms Describing the Role of the State and the Private Provision of Training - Andreas Kuhn; Jürg Schweri; Stefan C. Wolter (Institute of Labor Economics (IZA), 2019)
Apprenticeship systems are essentially based on the voluntary participation of firms that provide (and usually also finance) training positions, often incurring considerable net training costs. One potential, yet under-researched explanation for this behavior is that firms act in accordance with the norms and expectations they face with in the local labor market in which they operate. In this paper, we focus on the Swiss apprenticeship system and ask whether local norms towards the private, rather than the public, provision of training influence firms' decisions to offer apprenticeship positions. In line with this hypothesis, we find that the training incidence is higher in communities characterized by a stronger norm towards the private provision of training, which we measure using local results from two national-level plebiscites that explicitly dealt with the role of the state in the context of the apprenticeship system. This finding turns out to be robust to a series of alternative specifications and robustness checks, as well as to an instrumental-variable strategy that tackles the issue of potential endogeneity of normative attitudes.
Keywords: D22; D63; H41; I22; J24; 330; public goods; private provision of training; social norms; normative attitudes towards the role of the state; vocational education and training; apprenticeship training